Identification of Escherichia Coli Bacteria in Well Water Treatment at STIKes Namira Madina and Bottle Drinking Water - Simamora, Patimah (PT Inovasi Pratama Internasional, 2024)
Well water is one of the main sources of clean water supply for residents in STIKes Namira Madina. Well water has bacteriological qualities that are easily contaminated. Well water provides water that comes from the soil layer relative to the ground surface. Based on the Republic of Indonesia Minuster of Health Regulation no. 492 of 2010 concerning drinking water quality requirements states that the content of Escherichia coli bacteria in drinking water is 0/100 ml and for well water 10/100 ml. Drinking water and well water must not exceed specified requirements. This research aims to determine the quality of well water at STIKes Namira Madina and bottled drinking water. This research used descriptive experimental methods, sampling, bacterial identification, Gram staining, biochemical reaction tests, sugar medium test, triple sugar iron agar medium test, sulfur indole moltility medium test, urea agar medium test. of the 4 samples tested, 1 sample met the drinking water quality requirements according to the PERMENKES and the other 3 samples contained Escherichia coli bacteria in the well water at STIKes Namira Madina. The result of the 4 samples tested was only 1 sample that was suitable for drinking while the other 3 samples were not 3 samples contained Escherichia coli bacteria.